Smallfoot - Kirkpatrick, Karey; Reisig, Jason; Tatum, Channing; Corden, James; Zendaya, 1996-; Pablos, Sergio (Burbank, CA : Warner Bros. Entertainment, 2018)
A yeti stumbles upon a human whom his tribe believes to be legendary creatures called "smallfoot."
Originally released as a motion picture in 2018.
Based on the book "Yeti tracks" by Sergio Pablos.
Dolby digital 5.1, anamorphic wide screen 2.40:1.
Features: Yeti or not, here they come! : imagining Smallfoot.
Voices: Channing Tatum, James Corden, Zendaya, Common, LeBron James.
MPAA rating: PG.
Keywords: Pablos, Sergio -- Film adaptations; Yeti -- Drama; Action and adventure films; Computer animation films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Based on the book; Feature films; Animated films; Comedy films